The effects of emotional competence training on leaders' emotional intelligence and self-motivation in an organization - Halimah Mohd. Yusof, 1977-; Hamdan Abdul Kadir, supervisor; Mastura Mahfar; Fakulti Pengurusan (2014)
Thesis (Ph.D (Pengurusan)) - Universiti Teknologi Malaysia, 2014